Dietary Phosphorus Requirement of Giant Gouramy (Osphronemus gouramy Lac.) - M. Agus Suprayudi; Mia Setiawati (Jurnal Akuakultur Indonesia)
This experiment was conducted to ditermined phosphorus content in the feed of giant gouramy (Osprhonemus gouramy). Four semipurified diet containing isoprotein (41,0%) and isoenergy (10.0 kcal/g protein) but different in phosphorus content were prepared. Diet containing phosphorus at the level of 0,32, 0,63, 0,89 and 1,06% respectively. Fish weighing 21-25 g/ind was stocked at a density of 4 ind./aquarium. Fish was fed at a satiation level three times daily. Fish were reared for 40 days and sampling was done in every 10 day. Result of this study shows that growth performance of fish were increase with the increasing of phosphorus level in the diet till of level (0,89%). Make up of rate phosphor more than 1,06% in the diet will negating the growth. It can be concluded that giant gouramy require phosporus at the level of 0,63-0,89% for maximal growth.